Research in motion : compromise BlackBerry security, or give up emerging markets? - Bagley, Constance E.; Gunz, Sally; Smith, Andrea Nagy ([London] : SAGE, 2016)
In 2010, Research in Motion's BlackBerry offered its corporate clients the ultimate in smartphone security. All messages were encrypted before leaving the device and then were routed through a series of Network Operating Centers located in Canada. This made it difficult for government officials or private parties to eavesdrop on BlackBerry calls, texts, or e-mails. Sound security was one of the strategic advantages of the BlackBerry over other wireless devices. Customers were confident that their sensitive communications could be kept private anywhere in the world. As a result, the BlackBerry was the device of choice for military and other government, medical, and corporate clients. This case study discusses this topic.
Originally Published in: Bagley, C. E., Gunz, S., & Nagy Smith, A. (2011). Research in Motion: Compromise BlackBerry Security, or Give up Emerging Markets? (revised 12/05/2012). 11-011. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Research in Motion (Firm); Quality of products -- Case studies; Technology -- Marketing -- Case studies; Business and politics -- Case studies; Corporations -- Growth -- Case studies; BlackBerry (Smartphone)